A conceptual study of immigrant born globals and their multinationalization process - Ranfeng Qiu; Vipin Gupta (Journal of Global Entrepreneurship Research, 2015)
We build on the growing interest in born globals by examining the multinational growth pattern of immigrant new ventures, as opposed to that of native entrepreneurial new ventures. The multinational growth pattern of native new ventures, especially those originating from small home markets and/or lacking international market experience or networks, has been explained in the international business (IB) research using the Uppsala stage model. The Uppsala model postulates that the new ventures build their international absorptive capacity for discovering and accessing external knowledge by focusing on the psychically proximate nations and using low committed entry and growth modes, and then taking calculated risks to escalate their distance and commitment in a linear mode to reap positive rewards. We draw on the immigrant entrepreneur, social network, and related literatures to postulate that new immigrant ventures are more likely to be able to enter host markets that are psychically distant from their home markets and using higher committed entry and growth modes. Moreover, their founders are more likely to be cognitively and emotionally comfortable in pursuing non-linear approaches to sequential market entry and commitment mode choices. We discuss the implications of the varying balance of home vs. host market forces on the multinationalization process of alternative types of firms discussed in the literature.
Keywords: 650; Immigrant entrepreneurship; Born globals; Internationalization process